A parametric investigation on the shear strength and bearing capacity of Cenozoic Berea Red Sand with geosynthetic reinforcements - Van Rooy, J.L. (Jan Louis) (University of Pretoria, 2023)
Dissertation (MSc (Engineering Geology))--University of Pretoria, 2021.